Effect of food thermal processing on the composition of the gut microbiota - Pérez-Burillo, Sergio; Pastoriza, Silvia; Jiménez Hernández, Nuria; D'Auria, Giuseppe; Francino, Maria Pilar; Rufián-Henares, José Ángel; Francino (American Chemical Society, 2018)
Cooking modifies food composition due to chemical reactions. Additionally, food composition shapes the human gut microbiota. Thus, the objective of this research was to unravel the effect of different food cooking methods on the structure and functionality of the gut microbiota. Common culinary techniques were applied to five foods, which were submitted to in vitro digestion-fermentation. Furosine, HMF (5- hydroxymethyl-furfural) and furfural were used as Maillard reaction indicators to control the heat treatment. Short chain fatty acids production was quantified as indicator of healthy metabolic output. Gut microbial community structure was analyzed through 16S rRNA. Both food composition and cooking methods modified the microbiota composition and release short chain fatty acids. In general, intense cooking technologies (roasting and grilling) increased the abundance of beneficial bacteria like Ruminococcus spp. or Bifidobacterium spp. compared to milder treatments (boiling). However, for some foods (banana or bread) intense cooking decreased the levels of healthy bacteria.
“This document is the Accepted Manuscript version of a Published Work that appeared in final form in Journal of Agricultural and Food Chemistry, copyright © 2018 American Chemical Society after peer review and technical editing by the publisher. To access the final edited and published work see https://pubs.acs.org/doi/10.1021/acs.jafc.8b04077.”
Keywords: Alimentos - Microbiología; Alimentos procesados; Cooking; Maillard reaction; Food processing; Gut microbiota; Metagenomics